The role of genetic factors in the pathogenesis and course of familial Mediterranean fever (periodic illness) in residents of the Republic of Dagestan - E. M. Esedov; F. D. Ahmedova; D. S. Akbieva; A. S. Abasova (Лечащий Врач, 2024)
Background. Periodic illness, or familial Mediterranean fever, is a monogenic hereditary disease with an autosomal recessive mode of inheritance, which is characterized by spontaneous recurrent attacks of fever and aseptic inflammation of the serous membranes – polyserositis: peritonitis, pleurisy, synovitis. Its main and most severe complication is systemic amyloidosis, in particular, amyloid nephropathy with progressive chronic renal failure in the absence of treatment. The second complication of periodic illness, is adhesive disease, often with the development of small bowel obstruction and infertility. The disease is most common among representatives of the ancient peoples of the Mediterranean and is more common among Sephardic Jews, Armenians, Arabs, Greeks, Turks, Caucasian peoples.Results. The article presents modern approaches to the etiopathogenesis, diagnosis and treatment of familial Mediterranean fever (periodic illness), considers the clinical and genetic aspects, and also presents clinical cases from our own observations. Studied the ethnic composition and family history of patients to find out the frequency of family cases of this disease. The group consisted of 26 patients aged 16 to 74 years, including 14 men (54%) and 12 women (46%), who were examined in the gastroenterology department of the Republican Clinical Hospital of the Republic of Dagestan in the period 2011-2021. All patients were admitted to the department in the interictal period with complaints – of recurrent attacks of intense abdominal pain accompanied by febrile fever. When conducting general clinical and laboratory-instrumental research and taking into account the data of the anamnesis, another pathology was excluded and a diagnosis of «periodic illness» was made using the diagnostic criteria of the Tel Hashomer clinic.